Age-at-onset and association with clinical features in bipolar inpatients: A case-records-based study from a tertiary hospital in eastern part of Nepal (Journal of Psychiatrists' Association of Nepal, 2017)
Introduction: There are suggestions that age-at-onset (AAO) of bipolar disorder may differ geographically and (AAO) may influence the clinical characteristics. Lack of any published data from eastern part of Nepal prompted this studyObjective: The aim of the study was to find the mean AAO in admitted patients in a tertiary care hospital from eastern part of Nepal and to study the association of clinical variables with AAO.Method: Retrospective analysis was done of bipolar in-patients’ case-records (N=229) who were discharged from 2012 to 2014. Diagnosis was based on International Classification of Diseases, Clinical Descriptions and Diagnostic Guidelines, tenth version (ICD-10). All variables from files were noted in a Performa prepared by the department for the purpose. Mean AAO was determined. The association of early-onset (below or equal to 18 years of age) and late-onset (later than 18 years) with clinical variables (comorbidity, family history, lifetime presence of psychosis and suicidal attempts) was assessed with Chi-Square test (0.05).Result: Mean AAO was 23.97 (SD 8.7) years. AAO was significantly associated with comorbidity and not significantly associated with family history of bipolar disorder, lifetime presence of psychotic symptoms or suicidal attempt(s).Conclusion: AAO and comorbidity are associated. Present findings need to be seen with the limitation of the study.